∫
0
2
π
x
ln
2
(
sin
2
x
)
d
x
=
B
π
A
ln
C
(
D
)
+
F
π
E
If the above integral is true for positive integers:
A
,
B
,
C
,
D
,
E
,
F
and
D
is a prime, find:
A
+
B
+
C
+
D
+
E
+
F
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Erm. How? Can you show your working so I print it out ;)
Log in to reply
@Pi Han Goh now you happy!!?? ;)
@Pi Han Goh Did you print !!?? :P and is the answer clean??
Log in to reply
I'm still reading it. It's not easy to read through it when I don't know integrals.
Nice problem @Upanshu Gupta . I learnt about digamma function. I searched the internet for the proof of the following relation ψ ( x ) = ∫ 0 ∞ ( t e − t − 1 − e − t e − x t ) d t and ψ ( n ) = H n − 1 − γ . But I didnt find the proof anywhere. Can you please let me know the proof? Or let me know the better where I can find proof for all these types of Transcendental Functions.
Yep. It's correct. I've read it over 15 time and I can't find a mistake. Let me on my printer! Thanks!
now solve this . don't give the answer just solve with a solution
0 ∫ π / 2 x lo g 2 ( s i n x ) d x
Problem Loading...
Note Loading...
Set Loading...
The answer is: 8 π 2 ln 2 ( 2 ) + 9 6 π 4 The SOLUTION
I = ∫ 0 2 π x ln 2 ( sin 2 x ) d x Using f ( a + b − x ) = f ( x ) and adding the original and transformed integral, we get: I = 4 π ∫ 0 2 π ln 2 ( s i n ( 2 x ) ) d x = 4 π ∫ 0 2 π ln 2 ( 2 sin ( x ) cos ( x ) ) d x Expanding the square term and separating terms; we get I = ∫ 0 2 π [ ln 2 ( 2 ) + 2 ln 2 ( sin ( x ) ) + 4 ln ( 2 ) ln ( sin ( x ) ) + 2 ln ( sin ( x ) ) ln ( cos ( x ) ) ] d x where the fact that sin ( x ) = cos ( 2 π − x ) is used.
Further evaluating elementary integrals, and that integral of logarithm of sine and cosine over 0 to π / 2 is − 2 π ln ( 2 ) , we get: I = − 8 3 π 2 ln 2 ( 2 ) + 2 π ⎣ ⎢ ⎢ ⎡ K ∫ 0 π / 2 ln 2 ( sin ( x ) ) d x + L ∫ 0 π / 2 ln ( sin ( x ) ) ln ( cos ( x ) ) d x ⎦ ⎥ ⎥ ⎤ Now to evaluate these integrals, the main work starts: Consider the following integral ℑ ( a , b ) = ∫ 0 π / 2 sin a ( x ) cos b ( x ) d x = 2 Γ ( 2 a + b + 2 ) Γ ( 2 a + 1 ) Γ ( 2 b + 1 ) Differentiating above partially first w.rt a and then w.r.t b , we get ∂ a ∂ b ∂ ℑ ( a , b ) = ∫ 0 π / 2 sin a ( x ) cos b ( x ) ln ( sin ( x ) ) ln ( cos ( x ) ) d x = 8 1 Γ ( 2 a + b + 2 ) Γ ( 2 1 + a ) Γ ( 2 b + 1 ) [ − ψ ′ ( 2 a + b + 2 ) + [ ψ ( 2 b + 1 ) − ψ ( 2 a + b + 2 ) ] [ ψ ( 2 1 + a ) − ψ ( 2 a + b + 2 ) ] ] where Γ ( x ) is the Gamma Function and ψ ( x ) and ψ ′ ( x ) are the Digamma and Trigamma Functions Respectively.
Now, Plugging a = 0 and b = 0 , we get: L = ∫ 0 π / 2 ln ( sin ( x ) ) ln ( cos ( x ) ) d x = − 4 8 π 3 + 2 π ln 2 ( 2 ) where, the fact that: Γ ( 1 / 2 ) = π , ψ ( 1 ) = − γ , ψ ( 1 / 2 ) = − 2 ln ( 2 ) − γ and ψ ′ ( 1 ) = 6 π 2 are used. Here, γ is the Euler Mascheroni Constant.
Now H n is the Harmonic Number and
For evaluating ψ ′ ( 1 ) , the following consideration was used: ψ ( n ) = H n − 1 − γ Differentiating w.r.t n ; ψ ′ ( n ) = ( H n − 1 ) ′ but as H n − 1 = ∫ 0 1 1 − x 1 − x n − 2 d x ψ ′ ( n can be calculated. Now , for calculating K , the integral: ℑ ( a ) = ∫ 0 π / 2 sin a ( x ) d x is used and is Differentiated twice.This has been left as an exercise to the reader. The intregral comes out to be: K = ∫ 0 π / 2 ln 2 ( sin ( x ) ) d x = 2 π ln 2 ( 2 ) + 2 4 π 3 So, the final Integral Comes out to be: ∫ 0 2 π x ln 2 ( sin 2 x ) d x = 8 π 2 ln 2 ( 2 ) + 9 6 π 4